Potential Role of Insulin-Like Growth Factors in Myofascial Pain Syndrome: A Narrative Review. (21st December 2022) - Grosman-Rimon, Liza; Vadasz, Brian; Bondi, Moshe; Cohen, Marc; Santos, Sara; Katz, Joel; Clarke, Hance; Singh, Simranjit; Rimon, Jordan; Kumbhare, Dinesh; Eilat-Adar, Sigal
Abstract: Insulin-like growth factors have diverse functions in skeletal muscles by acting through multiple signaling pathways, including growth regulation and differentiation, anti-inflammation, and antioxidation. Insulin-like growth factors have anti-inflammatory effects and also play roles in nociceptive pathways, determining pain sensitivity, in addition to their protective role against ischemic injury in both the nervous system and skeletal muscle. In skeletal muscle, insulin-like growth factors maintain homeostasis, playing key roles in maintenance, accelerating muscle regeneration, and repair processes. As part of their maintenance role, increased levels of insulin-like growth factors may be required for the repair mechanisms after exercise. Although the role of insulin-like growth factors in myofascial pain syndrome is not completely understood, there is evidence from a recent study that insulin-like growth factor 2 levels in patients with myofascial pain syndrome are lower than those of healthy individuals and are associated with increased levels of inflammatory biomarkers. Importantly, higher insulin-like growth factor 2 levels are associated with increased pain severity in myofascial pain syndrome patients. This may suggest that too low or high insulin-like growth factor levels may contribute to musculoskeletal disorder process, whereas a midrange levels may optimize healing without contributing to pain hypersensitivity. Future studies are required to address the mechanisms of insulin-like growth factor 2 in myofascial pain syndrome and the optimal level as a therapeutic agent.